A novel inertial sensor exploiting magnetic fluid. (September 2019) - Zhang, X; Xia, X; Zhang, W; Xiang, Z
Abstract: Narrow available frequency range and low linearity of traditional magnetic fluid inertial sensors make them unpractical. A novel inertial sensor exploiting magnetic fluid is designed to solve these shortcomings. Through simulation and experiments, characteristics of magnetic fluid such as damping effect and levitation effect are studied. It shows that magnetic fluid has excellent damping effect which can be controlled by magnetic field. In order to improve the frequency response, both levitation and damping effect are used in sensors. Cylindrical permanent magnet is employed as the inertial mass, which can transform acceleration to the change of magnetic field. Linear hall sensor with high sensitivity is the transducer installed on the position where magnetic field gradient of cylindrical permanent magnet is maximal and has best linearity. Verification experiments of the designed sensor are conducted on vibration platform. Experimental results give that application of magnetic fluid for inertial sensor optimizes its performance greatly. Available frequency range of the designed sensor is increased by 256% after using magnetic fluid as damping material. This paper provides a reference for research on magnetic fluid and its application in inertial sensors.